P4 6 King Solar Power Stadium - Owusu Boamah, Jeremy; McCrea, Alec; Fotedar, Ayush (Physics Special Topics, 2024)
This study investigates the potential of photovoltaic (PV) systems to offset non-renewable energy use at Leicester’s King Power Stadium by harnessing solar power. Through modelling the perfor mance of a monocrystalline-silicon PV system installed on the stadium’s roof, we estimate that the system could provide renewable energy equivalent to 20% of the stadium’s annual energy demand.